Pengaruh Model Pembelajaran RME (Realistic Mathematics Education) pada Materi Bangun Datar Terhadap Kemampuan Numerasi Siswa Kelas VII SMPIT An-Nida’ Lubuklinggau - Aria Selfis (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to examine the effect of the Realistic Mathematics Education (RME) learning model on the numeracy skills of seventh-grade students at SMPIT An-Nida’ Lubuklinggau. The method used is an experimental approach with a quasi-experimental design. The population consisted of 54 seventh-grade students, divided into two groups: Class VII-2 as the experimental group and Class VII-3 as the control group. Data collection was conducted through observation, tests, and documentation. Data analysis techniques included prerequisite tests (normality test), Wilcoxon test, Mann-Whitney test, and N-Gain test. The results showed that the significance value (sig. 2-tailed) in the Independent Sample Wilcoxon and Mann-Whitney tests was 0.000, which is less than 0.05 (sig. 2-tailed ≤ 0.05). In conclusion, the Realistic Mathematics Education (RME) model positively influences the improvement of numeracy skills among seventh-grade students at SMPIT An-Nida’ Lubuklinggau. Keywords: Realistic Mathematics Education (RME), Numeracy Skills